2012
DOI: 10.1029/2011gl050197
|View full text |Cite
|
Sign up to set email alerts
|

Backwater controls of avulsion location on deltas

Abstract: [1] River delta complexes are built in part through repeated river-channel avulsions, which often occur about a persistent spatial node creating delta lobes that form a fan-like morphology. Predicting the location of avulsions is poorly understood, but it is essential for wetland restoration, hazard mitigation, reservoir characterization, and delta morphodynamics. Following previous work, we show that the upstream distance from the river mouth where avulsions occur is coincident with the backwater length, i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
270
3

Year Published

2013
2013
2015
2015

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 151 publications
(303 citation statements)
references
References 37 publications
30
270
3
Order By: Relevance
“…The maximum size of morphodynamic landforms also appears to scale with the advection length scale (LE10 4 l a ), which may ultimately be set by the size of the depositional system 10 since large systems tend to transport fine sediment and consequently have large advection length scales. For example, the dominant scale of river deltas is set by morphodynamic feedbacks that force river avulsion at a certain spatial node 37 ; thus the largest morphodynamic feedbacks occur at the size of the delta itself (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…The maximum size of morphodynamic landforms also appears to scale with the advection length scale (LE10 4 l a ), which may ultimately be set by the size of the depositional system 10 since large systems tend to transport fine sediment and consequently have large advection length scales. For example, the dominant scale of river deltas is set by morphodynamic feedbacks that force river avulsion at a certain spatial node 37 ; thus the largest morphodynamic feedbacks occur at the size of the delta itself (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…Both the adverse bed slope and topographic relief at this bifurcation should limit sand transport into the WLFC. Second, studies of the main stem Mississippi River have shown that during floods, the sediment transport must increase in the downstream direction [Chatanantavet et al, 2012;Lamb et al, 2012;Nittrouer et al, 2012]. These studies use capacity transport formulations, but any increase in sediment transport rate would require erosion of the bed.…”
Section: The Cover Effect and Supply-limited Channelsmentioning
confidence: 99%
“…However the total sand body extent will depend on the lateral connectivity between these sand rich features (Ravenne, et al 1989 (Ashworth, et al 2011), experimentally (Rowland, Dietrich and Stacey 2010) as well as numerically (Chatanantavet, Lamb and Nittrouer 2012;Nardin, et al 2013;Leonardi, et al 2013;Edmonds and Slingerland, 2007;Edmonds, et al 2010). Previous work on mouth bars, for example, includes their formation of river dominated delta networks (Edmonds and Slingerland, 2007) but there has also been studies focussed on sub-aqueous levee formation (Rowland, Dietrich and Stacey 2010).…”
Section: Theory and Methodsmentioning
confidence: 99%
“…The study does not explore whether this is also the case for delta systems and a similar study on deltaic deposits could be conducted. Chatanantavet, et al (2012) looked at the influence of variable river discharge on deposition in the river delta and found that it can have strong influences on the stratigraphy. Much work has been done on distributary channel networks in rivers and deltas (Kleinhans, et al 2013), but the focus of these studies have not been connectivity of sandy deposits.…”
Section: Theory and Methodsmentioning
confidence: 99%